1982
DOI: 10.1056/nejm198211183072101
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Prevention Study with Oxprenolol in Coronary Heart Disease

Abstract: We carried out a randomized double-blind controlled secondary-prevention trial of oxprenolol over seven years. Forty milligrams of oxprenolol or placebo was given twice daily to 1103 men 35 to 65 years old who had an acute myocardial infarction between 1 and 90 months previously. Overall, there was no difference in mortality or cardiac events between the placebo and oxprenolol groups. The major influence on prognosis was the time at which treatment was started after infarction. In 417 patients in whom treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Analogous results were fo und in randomized trials of practolol (58), timolol (62), and oxprenolol (72). In these four trials, relative reductions in mortality in the treated groups ranged from 27% to 45%.…”
Section: Effectivenessmentioning
confidence: 53%
See 1 more Smart Citation
“…Analogous results were fo und in randomized trials of practolol (58), timolol (62), and oxprenolol (72). In these four trials, relative reductions in mortality in the treated groups ranged from 27% to 45%.…”
Section: Effectivenessmentioning
confidence: 53%
“…In the past several years, four independent, randomized trials have found that beta-adrenergic blocking agents increase survival when administered soon after acute myocardial infarctions (MI) (4,58,62,72). No evidence, pro or con, has been reported to date on the ability of such drugs to reduce mortality in patients with stable angina, but the temporal trend toward increased survival among patients treated medically in trials involving bypass surgery (5,24,70) sug gests that beta blockade may be beneficial.…”
Section: Beta-blocking Drugsmentioning
confidence: 99%
“…A particular hope was that these agents might protect against coronary events (Robertson, 1978), a hope that was encouraged by their undoubted success when given after myocardial infarction (Robertson, 1983b; Norwegian Multicenter Study Group, 1981; Beta-Blocker Heart Attack Study Group, 1981;Hjalmarson et al, 1981;Editorial, 1982;Hampton, 1981). It was in this connection disconcerting to read in the introduction to the report (The IPPPSH Collaborative Group, 1985) that a major reason for selecting oxprenolol for evaluation was an earlier successful postinfarction study (Taylor et al, 1982) using that drug. The outcome of that earlier trial was a good deal less clear than the authors of IPPPSH imply; there was no overall difference in either mortality or cardiac events between the placebo and oxprenolol groups.…”
Section: Comments On Ipppshmentioning
confidence: 99%
“…Patients with 'definite' infarction assessed by Minnesota Code electrocardiographic criteria (Rose & Blackburn, 1968;Taylor et al, 1982), on admission to the Coronary Care Unit, were routinely monitored with a Swan-Ganz thermodilution catheter to detect clinically unrecognised heart failure. Patients found to be haemodynamically uncomplicated were requested to participate in this study and following informed consent allocated to receive 120 min infusion of lignocaine (Group I), disopyramide (Group II) or flecainide (Group III).…”
Section: Patientsmentioning
confidence: 99%